Ultrasound‐guided femoral arterial access in pediatric cardiac catheterizations: A prospective evaluation of the prevalence, risk factors, and mechanism for acute loss of arterial pulse. Issue 7 (18th August 2016) - Alexander, John; Yohannan, Thomas; Abutineh, Iman; Agrawal, Vijaykumar; Lloyd, Hannah; Zurakowski, David; Waller, B. Rush; Sathanandam, Shyam
Abstract : Objectives: The objectives of this study were to describe the prevalence, mechanisms, and identify risk factors for acute loss of arterial pulse (LOP) in children who had ultrasound‐guided femoral arterial access (UGFAA) during cardiac catheterization. Background: LOP is a known complication in children following femoral arterial (FA) access for cardiac catheterization. The prevalence of LOP requiring treatment ranges between 4% and 8%. Methods: A prospective study was performed including 486 cardiac catheterizations using UGFAA in children ≤18 years over a 3 years period. Ultrasound and Doppler evaluations were performed prior to and at the end of the procedure. Results: LOP was identified in 33 cases (6.8%) with 23 (4.7%) requiring treatment. For children ≤6 months, the prevalence of LOP requiring treatment was 13.6%. FA diameter <3 mm was the only significant independent predictor for LOP (OR: 8.44, 95% CI: 2.07–34.5, P  < 0.001). Smaller patient size, number of access attempts, time required for access, operator experience, sheath size, and length of procedure were not found to be significant predictors. Children with LOP had a greater percentage decrease in vessel diameter (median 62% vs 18%, P  < 0.001) compared to those without LOP. FA thrombus was diagnosed only in 9 patients (27% of those with LOP). Conclusions: The prevalence of LOP requiring treatment is 4.7% when UGFAA is used during pediatric cardiac catheterizations. Arterial spasm was more common than thrombus as a cause of LOP. FA diameter <3 mm was the only independent predictor for LOP in this carefully designed prospective study. © 2016 Wiley Periodicals, Inc.